2020
DOI: 10.1097/md.0000000000018779
|View full text |Cite
|
Sign up to set email alerts
|

d-dimer and diffusion-weighted imaging pattern as two diagnostic indicators for cancer-related stroke

Abstract: The aim of this study was to evaluate the risk factors and elucidate the clinical characteristics of cancer-associated ischemic stroke to differentiate it from conventional ischemic stroke in China and East Asia. Between June 2012 and June 2016, a retrospective analysis was performed on 609 stroke patients with cancer. They were divided into 3 groups: cancer-stroke group (CSG, 203 cases), stroke group (SG, 203 cases), and cancer group (CG, 203 cases). The d-dimer levels and diffusion-weighted imaging lesion (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Besides having specific clinical features, cancer‐related CI also has specific pathogenesis that is worth exploring. Previous studies have found that in addition to the fact that some cancers can directly lead to CI (Budincevic et al., 2016 , Zheng et al., 2014 ), most cancer‐related CI is associated with hypercoagulability based on elevated serum D‐dimer level (Shen et al., 2020 , Rosenberg et al., 2020 , Gon et al., 2017 ). However, as has been found in other studies on the pathogenesis of cancer‐related CI, although patients are considered to be hypercoagulable, routine coagulation tests, such as thrombin time, PT, APTT, and INR, are normal in most patients with cancer‐related CI, suggesting that the tests are inadequate to assess blood clotting (Cheng et al., 2021 , Quan et al., 2020 , Qin et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides having specific clinical features, cancer‐related CI also has specific pathogenesis that is worth exploring. Previous studies have found that in addition to the fact that some cancers can directly lead to CI (Budincevic et al., 2016 , Zheng et al., 2014 ), most cancer‐related CI is associated with hypercoagulability based on elevated serum D‐dimer level (Shen et al., 2020 , Rosenberg et al., 2020 , Gon et al., 2017 ). However, as has been found in other studies on the pathogenesis of cancer‐related CI, although patients are considered to be hypercoagulable, routine coagulation tests, such as thrombin time, PT, APTT, and INR, are normal in most patients with cancer‐related CI, suggesting that the tests are inadequate to assess blood clotting (Cheng et al., 2021 , Quan et al., 2020 , Qin et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…39 The DWI is commonly used to evaluate multipleterritory acute lesion patterns in patients with AF-related stroke or malignant disease. [20][21][22] DWI is particularly noted for its sensitivity (88%-100%) and specificity (86%-100%) in the early detection of small infarcts and thus has become a valuable tool for investigating ischemic stroke [20][21][22] and is commonly used in emergency department settings. 40 Cancer-related hypercoagulability is the underlying cause of CAT in 40% of affected patients.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in DWI lesion patterns between AF-related stroke and CAT may facilitate differential diagnosis and early treatment. [20][21][22] Manual interpretation of DWI images imposes a high burden of human effort and monetary cost, and automatic interpretation via machine learning appears to be a promising solution. Machine learning uses algorithms to imitate the way that humans learn, and the performance of these algorithms improves upon exposure to more data over time.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a multiple scattered lesion pattern, often reported in CAS, was associated to higher D-dimer values [ 17 , 18 , 19 ]. These findings support the link between infarction in multiple vascular territories and cancer-associated hypercoagulation as the underlying stroke mechanism.…”
Section: Discussionmentioning
confidence: 99%